IMPLEMENTASI PIDANA TANPA PENJARA TERHADAP PENGARUHNYA DALAM MENGATASI OVERCROWDING DI SELURUH UPT PEMASYARAKATAN INDONESIA - Wahyu Cahyo Wibowo; Mitro Subroto (Universitas Islam Darul Ulum Lamongan, 2022)
Correctional facilities which have the aim of forming Correctional Inmates to become fully human, realize mistakes, improve themselves and do not repeat criminal acts so that they can be re-accepted in society, in the view of the general public there are more negative stigmas, especially in terms of the icons of correctional facilities. , namely the Correctional Institution or Prison. A lot of news that is known by the public about prisons is negative news such as fires, riots, escapes and even overcrowding or overcapacity. This article will explain the factors, effects of alternative punishment in overcoming prison problems and their implementation in Indonesia. The research uses a normative juridical method which will seek the truth based on logic and actual circumstances.